TRANSACTIONAL LEADERSHIP STYLE IN IMPROVING TEACHER PERFORMANCE IN MI RAMBAY, SUKABUMI DISTRICT - Fatimah Nurjariah; Mulyawan Safwandy Nugraha (Media Inovasi Pendidikan dan Publikasi, 2023)
This study aims to determine the transactional leadership style in improving teacher performance at MI Rambay Sukabumi District, using descriptive qualitative reaseach methods and collecting data through in-depth interviews, observation and documentation studies, the results of this discussion are that the leadership style at MI Rambay in improving teacher performance is a transactional leadership style.